Folliculin: A Regulator of Transcription Through AMPK and mTOR Signaling Pathways - Ramirez Reyes, Josué M. J.; Cuesta, Rafael; Pause, Arnim (Frontiers in Cell and Developmental Biology, 2021)
FLCN is a tumor suppressor gene responsible for the inherited Birt-Hogg-Dubé (BHD) syndrome, which affects kidneys, skin and lungs. FLCN is a highly conserved protein that forms a complex with folliculin interacting proteins 1 and 2 (FNIP1/2). Although its sequence does not show homology to known functional domains, structural studies have determined a role of FLCN as a GTPase activating protein (GAP) for small GTPases such as Rag GTPases. FLCN GAP activity on the Rags is required for the recruitment of mTORC1 and the transcriptional factors TFEB and TFE3 on the lysosome, where mTORC1 phosphorylates and inactivates these factors. TFEB/TFE3 are master regulators of lysosomal biogenesis and function, and autophagy. By this mechanism, FLCN/FNIP complex participates in the control of metabolic processes. AMPK, a key regulator of catabolism, interacts with FLCN/FNIP complex. FLCN loss results in constitutive activation of AMPK, which suggests an additional mechanism by which FLCN/FNIP may control metabolism. AMPK regulates the expression and activity of the transcriptional cofactors PGC1/, implicated in the control of mitochondrial biogenesis and oxidative metabolism. In this review, we summarize our current knowledge of the interplay between mTORC1, FLCN/FNIP, and AMPK and their implications in the control of cellular homeostasis through the transcriptional activity of TFEB/TFE3 and PGC1/. Other pathways and cellular processes regulated by FLCN will be briefly discussed.